Ù‚Ø¯Ø±Ø© ØÙØ¸ Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… ÙˆØ¹Ù„Ø§Ù‚ØªÙ‡Ø§ ÙÙŠ Ø³Ù‡ÙˆÙ„Ø© ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø¯Ù‰ Ø·Ø§Ù„Ø¨Ø§Øª Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø¹Ø§Ù„ÙŠ Ù„Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ÙˆØ§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Rahmayani, Rahmayani; Arsyad, Aisyah; Hamka, Hamka (Ø§Ù„Ø¨ØµÙŠØ±Ø©: Ù…Ø¬Ù„Ø© Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©, 2021)
This thesis discusses the relationship between the ability of memorizing the Al-Qur'an al-kariim and the easeness of Arabic learning for female students at STIBA Makassar. The main objectives of this research were threefolds: 1. To understand the female students’ ability in memorizing the Al-Qur'an al-kariim at STIBA Makassar, 2. To understand the processes of the Arabic learning and the Al-Qur'an al-kariim memorization activities of female students at STIBA Makassar, 3. To investigate the relationship between the Al-Qur'an al-kariim memorization ability and the easiness of Arabic learning for female students at STIBA Makassar. The researcher completed this study by using a qualitative descriptive method with a semi-quantitative approach. The data collection methods used in this research were personal interviews and accurate observations on the students’ learning process. The data of students’ academic assessments who were successful in one semester were collected and analysed. The quantitative data were also collected in this research from the answers of students through compatibility approach. From this research, it was apparent that the methods used by the teachers and students in memorizing the Al-Qur'an al-kariim was considered to be very good. In terms of the relationship between the Al-Qur'an al-kariim memorization and Arabic learning, 100% of teachers and 97.9% of female students at STIBA Makassar were in agreement that there is a strong and close relationship between the Al-Qur'an al-kariim memorization and Arabic learning. In this case, the Al-Qur'an al-kariim memorization could assist students to understand the Arabic language and context and to pronounce the Arabic words and letters contained in the verses of the Al-Qur'an al-kariim. Besides, the non-Arabic Al-Qur'an al-kariim memorizers are able to learn Arabic easily because by memorizing the Al-Qur'an al-kariim, a memorizer applies and practices various aspects that could better their Arabic such as the four language skills, the Arabic elements, and the contexts of religious lessons and understandings.